Validation of vibration reduction in barge-type floating offshore wind turbines with oscillating water columns through experimental and numerical analyses - Aboutalebi, Payam; Garrido, Aitor J.; Schallenberg-Rodriguez, Julieta; Garrido, Izaskun (Frontiers in Built Environment, 2024)
Floating offshore wind turbines (FOWTs) are highly susceptible to vibrations caused by wind and sea wave oscillations, necessitating effective vibration reduction strategies to ensure stability and optimal performance. This study investigates the effectiveness of a barge-type FOWT integrated with oscillating water columns (OWCs) in reducing oscillations, particularly in rotational modes. A hybrid FOWT-OWCs system was designed, and its vibration mitigation capabilities were assessed through both numerical simulations and experimental tests. The numerical approach focused on controlling airflow in the OWCs, while the experimental tests validated these results under similar conditions. A strong agreement between the simulations and experiments was observed, particularly in reducing platform pitch oscillations, even under irregular wave conditions. The open OWC-based platform outperformed the closed design, reducing pitch angle oscillations from 17.51° to 14.38° for waves with a 10-s dominant frequency. Benchmark tests confirmed this trend, with the open moonpool-based platform achieving a reduction from 18.41° to 12.23°. These findings demonstrate the potential of OWCs to improve the stability and performance of FOWTs, with experimental validation providing confidence in the numerical predictions.